Indonesian Sound Errors in Television Advertisements - Erwina, Emmy; Syarfina, Tengku; Chitra, Bima Prana (Universitas Pendidikan Ganesha, 2024)
Language sound errors at the phonological level. Phonemes or language sounds in Indonesian consist of vowels, consonants, diphthongs 'double vowels', and clusters 'consonant groups'. Differences in phonemes will change standard language varieties into non-standard ones. Phonological problems occur because vowel, consonant or diphthong phonemes change into other phonemes, thereby changing standard language into non-standard ones. This research aims to analyze language sound errors, namely deletions, additions and changes in vowel phonemes, consonant phonemes, combined vowel phonemes and combined consonant phonemes. This study used descriptive qualitative method. The data collection technique for this research is by listening and using the language watched in Indonesian television advertisements. This data analysis technique consists of (1) data collection (2) data reduction, (3) data presentation (4) interesting conclusions. The results of data analysis of Indonesian language sound errors in Television Advertisements are language sound errors in Indonesian consisting of vowels, consonants, diphthongs 'double vowels', and 'consonant clusters' clusters due to errors in language use that do not match Indonesian Spelling (EBI) . Errors in Indonesian sounds or pronunciation that occur in television advertisements like this occur due to ignorance or on purpose so that the advertisement displayed will attract the attention of consumers or people who see, watch and listen to it.